"Water‐in‐Salt" Nonalkaline Gel Polymer Electrolytes Enable Flexible Zinc‐Air Batteries with Ultra‐Long Operating Time. (15th June 2022) - Zhang, Yanan; Wu, Dingsheng; Huang, Fenglin; Cai, Yibing; Li, Yonggui; Ke, Huizhen; Lv, Pengfei; Wei, Qufu
Abstract: Solid‐state zinc‐air batteries (ZABs) are regarded as one of the most promising flexible energy storage systems for wearable electronic devices beyond lithium‐ion batteries. Unfortunately, continuous water loss of electrolyte and zinc electrode corrosion severely limit service life of ZABs. Herein, a "water‐in‐salt" (WIS) nonalkaline gel polymer electrolyte with a double network (polyacrylic acid and cellulose nanofibers) is prepared in one step via UV light‐initiated free radical polymerization. The WIS electrolyte is realized by coordination interactions between zinc trifluoromethylsulfonate and acetamide and exhibits extraordinary thermodynamic stability. Benefiting from strong interactions between water and other components, the electrolyte can capture water from ambient air and realize dynamic balance of adsorption and desorption. Therefore, flexible ZAB achieves an ultra‐long cycle time of 1300 h. In addition, the gel polymer electrolyte possesses excellent adhesion property and can be tightly bonded to the electrodes without fixation measures. The fabricated sandwich‐ and cable‐type batteries adapt to complex deformations without sacrificing electrochemical performance, which demonstrates enormous potential for practical wearable applications. Abstract : A "water‐in‐salt" nonalkaline gel polymer electrolyte is obtained via coordination interactions between zinc trifluoromethylsulfonate and acetamide. Extraordinary thermodynamic stability drives the electrolyte to capture water from ambient air and realize a dynamic balance between adsorption and desorption. The prepared flexible zinc‐air battery exhibits an ultra‐long cycle time of 1300 h.